The impact of project management skills on the performance of renewable energy projects - Norhanim Zakaria,; Nazanin Ahmadian, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Project management skills are critical in ensuring the success of energy management project. Amongst project management skills, three were identified important in managing renewal energy projects. They were managing human resources, transformational leadership and knowledge sharing. These constructs were influential factors that capable of affecting energy project performance. Such impact could be by increasing motivation in projects’ employees. Previous studies recorded 11 variables that had been considered for those 3 project management skills constructs. Palm and oil mills projects had been selected for the data collection. Eighty-six (86) data from palm and oil mills located in Peninsular have been collected through questionnaire and respondents involved majority were the project managers. This study employed quantitative research design. Pearson Correlation Coefficient test was used to establish relationships between three project management constructs towards renewable energy project success. The results showed that all three constructs were significantly correlated with energy project performance. For HRM practices, the maximum impact was for training and the minimum impact was variable related to staffing. Among variables for transformational leadership, vision recorded the strongest relationship on energy project success. In addition, both variables for knowledge sharing have significant positive impact on energy project performance. It could be concluded that all three project management skills are important for palm and oils mill projects in improving energy project performance.